The Role of Law Clinics and Legal Aid Center in Providing Legal Aid for Vulnerable Group: A Case of Africa, Indonesia, and Australia - Akintunde, Daniel; Choirunnisa, Sutiani; Fernando, Christoper Bastiaan (The Indonesian Journal of International Clinical Legal Education, 2022)
Legal aid is a concept in response to the community's need for the adage "law is sharp down, blunt up". The existence of Law Number 16 of 2011 concerning Legal Aid cannot be separated from the legal reform agenda that gives citizens the right to obtain justice and the right to a fair and impartial trial, including through the provision of legal aid. Legal aid is part of the advocate profession which is a noble profession or officium nobile because it requires the defense of all people regardless of background, race, skin color, religion, culture, socioeconomic, rich-poor, belief, politics, gender, and ideology.